Cardiomyocyte stromal interaction molecule 1 is a key regulator of Ca2+‐dependent kinase and phosphatase activity in the mouse heart. Issue 4 (18th February 2022) - Collins, Helen E.; Anderson, Joshua C.; Wende, Adam R.; Chatham, John C.
Abstract: Stromal interaction molecule 1 (STIM1) is a major regulator of store‐operated calcium entry in non‐excitable cells. Recent studies have suggested that STIM1 plays a role in pathological hypertrophy; however, the physiological role of STIM1 in the heart is not well understood. We have shown that mice with a cardiomyocyte deletion of STIM1 ( cr STIM1 −/− ) develop ER stress, mitochondrial, and metabolic abnormalities, and dilated cardiomyopathy. However, the specific signaling pathways and kinases regulated by STIM1 are largely unknown. Therefore, we used a discovery‐based kinomics approach to identify kinases differentially regulated by STIM1. Twelve‐week male control and cr STIM1 −/− mice were injected with saline or phenylephrine (PE, 15 mg/kg, s.c, 15 min), and hearts obtained for analysis of the Serine/threonine kinome. Primary analysis was performed using BioNavigator 6.0 (PamGene), using scoring from the Kinexus PhosphoNET database and GeneGo network modeling, and confirmed using standard immunoblotting. Kinomics revealed significantly lower PKG and protein kinase C (PKC) signaling in the hearts of the cr STIM1 −/− in comparison to control hearts, confirmed by immunoblotting for the calcium‐dependent PKC isoform PKCα and its downstream target MARCKS. Similar reductions in cr STIM1 −/− hearts were found for the kinases: MEK1/2, AMPK, and PDPK1, and in the activity of the Ca 2+ ‐dependent phosphatase, calcineurin. Electrocardiogram analysis also revealed that cr STIM1 −/− mice have significantly lower HR and prolonged QT interval. In conclusion, we have shown several calcium‐dependent kinases and phosphatases are regulated by STIM1 in the adult mouse heart. This has important implications in understanding how STIM1 contributes to the regulation of cardiac physiology and pathophysiology. Abstract : Little is known of the physiological role of stromal interaction molecule 1 (STIM1) in the heart and the signaling pathways it regulates. Here, we show that hearts lacking cardiomyocyte STIM1 have reduced activities of several calcium‐dependent kinases and phosphatases, which impact cardiac electrophysiology. Collectively, these results suggest a novel role for STIM1 in regulating cardiac homeostasis.